The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1007/s002469900318
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Prevention of Neurological Complications in Pediatric Cardiac Surgery

Abstract: Because of advances in surgical and cardiopulmonary bypass techniques it is now possible to definitively repair the vast majority of congenital heart disease in infancy or childhood. Although the majority of survivors do not have obvious cerebral sequelae, there is increasing disquiet about the high incidence of acute neurological events in the immediated postoperative period as well as evidence that at long-term follow-up there are subtle cognitive and motor deficits in many. Some children are more at risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 192 publications
0
40
0
Order By: Relevance
“…29,33 Specific in utero and perioperative neuroprotective strategies to achieve these goals should be further investigated. 49,50 The strengths of this study include the high proportion of children assessed at 4. …”
Section: Figurementioning
confidence: 99%
“…29,33 Specific in utero and perioperative neuroprotective strategies to achieve these goals should be further investigated. 49,50 The strengths of this study include the high proportion of children assessed at 4. …”
Section: Figurementioning
confidence: 99%
“…105,164,166,168,169 Severe neurological complications are more common in children who have HLH [170][171][172][173] after surgery in younger infants (<3 months old), 171 in operations involving the aortic arch, 81 in surgery that is complicated by multiple organ failure 174 and possibly in acyanotic heart malformations. 175 As children grow older, the frequency of diagnosis of neurodevelopmental problems increases, particularly of neurological deficits (nerve palsies, dyspraxias, seizures, etc.)…”
Section: Neurological Outcomesmentioning
confidence: 99%
“…Newburger et al [14], in a study of hypothermic circulatory arrest versus low-flow bypass, demonstrated that seizures are important indicators of neurodevelopmental outcome, and seizures were higher in patients with circulatory arrest. Even though the rate of postsurgical stroke is known in HLHS patients, the incidence of medically intractable seizures in those patients who underwent Fontan operation is unknown [13,15,16,17]. …”
Section: Discussionmentioning
confidence: 99%